2016
DOI: 10.1016/j.meatsci.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of beef from immunocastrated (BOPRIVA ® ) Nellore bulls

Abstract: Twenty Nellore bulls (ABW=357.7±9.65kg) were divided into 2 groups: intact and immunocastrated - Bopriva®. After the trial period, the cattle were slaughtered and carcass fat thickness was evaluated, ether extract and fatty acid composition of the longissimus thoracis analyses were performed, and the activity indices of relevant enzymes were calculated. The means were calculated and compared by Student's t-test and Pearson's correlation coefficients (p<0.05). The immunocastrated group showed higher back fat th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
2
9
1
3
Order By: Relevance
“…Bulls had the highest average of n6 FAs, which affected the n6/n3 ratio (Table ), but the n6/n3 ratio was within the recommended range considered beneficial to human health in all studied groups. Andreo et al () also found higher level of n6 FAs in bulls compared to the immunocastrated group, but this value did not affect the n6/n3 ratio, contrary to our results. The recommended dietary n6/n3 ratio is 4.0 or less (Wood et al, ), because a high intake of n6 FAs promotes cardiovascular diseases, inflammatory disorders, and cancers (Horrobin, Jenkins, Bennett, & Christie, ).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Bulls had the highest average of n6 FAs, which affected the n6/n3 ratio (Table ), but the n6/n3 ratio was within the recommended range considered beneficial to human health in all studied groups. Andreo et al () also found higher level of n6 FAs in bulls compared to the immunocastrated group, but this value did not affect the n6/n3 ratio, contrary to our results. The recommended dietary n6/n3 ratio is 4.0 or less (Wood et al, ), because a high intake of n6 FAs promotes cardiovascular diseases, inflammatory disorders, and cancers (Horrobin, Jenkins, Bennett, & Christie, ).…”
Section: Resultscontrasting
confidence: 99%
“…The levels of linoleic, docosatrienoic, eicosadienoic, and eicosatrienoic FAs were higher ( p < 0.01) in bull meat compared to other groups (Table ). Recently, Andreo et al () also observed higher levels of linoleic FA in the meat from bulls compared to the immunocastrated group, whereas Monteiro, Santos‐Silva, Bessa, Navas, and Lemos () reported higher linoleic levels in bull meat compared to steer, which agrees with our results. These results may be explained by the higher fat deposits on the carcass of heifers, steers and immunocastrated animals and, according to Eguinoa et al () one important consequence of increased fat deposition is that the phospholipid proportion reduces, leading to decreasing PUFA levels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Ruiz et al (2005), reportaram maiores valores de lipídios totais em animais CC, seguido por IC e um menor valor para NC. Além disso, Andreo et al (2013Andreo et al ( , 2016 Tabela 5. Medias, erro padrão da media (EPM) e probabilidade das características sensoriais da carne avaliada por teste afetivo de aceitação do consumidor, de acordo com a condição sexual.…”
Section: Lipídios Totais E Tbarsunclassified
“…Nelore) castrados produziram carne com melhores características de cor e maciez objetiva (medida por força de cisalhamento) quando comparados com não-castrados (inteiros), embora não tenham sido observadas diferenças em maciez sensorial (medida por teste sensorial). Nesses estudos, foram utilizados bovinos Nelore puros com idade inicial de 24 meses(Martínez et al, 2017;Andreo et al, 2016) ou bovinos Angus-Nelore(Miguel et al, 2014) de mesma idade, ambos terminados em confinamento por no máximo 90 dias. De forma semelhante, nesta abordagem foi verificado se as variáveis acabamento e classe sexual influenciariam nas respostas da satisfação geral dos consumidores de carne bovina, sendo utilizado o índice de Marcotorchino para mensurar tais associações.…”
unclassified